Quality of life, depressive and minor psychiatrics symptoms in nursing students - Jéssica Morgana Gediel Pinheiro; Andreia Barcellos Teixeira Macedo; Liliana Antoniolli; Thayane Martins Dornelles; Juliana Petri Tavares; Sonia Beatriz Cocaro de Souza (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To assess quality of life, prevalence of depressive and minor psychiatric symptoms in Nursing students. Methods: Cross-sectional study, conducted from March to April 2018, at a federal university. Sample composed of 242 Nursing students, from the 1st to the 8th semester. Data was collected using the quality of life instruments, Beck Depression Inventory and Self-Report Questionnaire. A significance level of 0.05 was considered. Results: The mean age was 22.9 ± 5.1 years. It was found that 25% of the students had severe depressive symptoms and 54% of the students had minor psychiatric disorders, with a higher prevalence in the first semesters. An inverse relationship was observed between the frequency of depressive symptoms and quality of life scores (p = 0.05). Conclusion: Nursing students showed a high prevalence of depressive symptoms, indicating the importance of implementing actions to promote and prevent mental health.